2021
DOI: 10.1111/1745-9125.12295
|View full text |Cite
|
Sign up to set email alerts
|

Sex, drugs, and coercive control: Gendered narratives of methamphetamine use, relationships, and violence

Abstract: While many of the motives people provide for using drugs transcend gender, there are also notable gendered differences. These differences in motive talk aid in stigma management, shape gender performances, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…The regular use of meth among the women participants put them at risk of being heavily stigmatized. Their social positions also often resulted in others (mostly men) seeking to control their lives and drug use (see Copes et al, 2022). Although this affected participants' sense of agency and autonomy, they did not passively accept this stigma or the corresponding control over their lives.…”
Section: How Symbolic Boundaries Reduce Harmmentioning
confidence: 99%
See 1 more Smart Citation
“…The regular use of meth among the women participants put them at risk of being heavily stigmatized. Their social positions also often resulted in others (mostly men) seeking to control their lives and drug use (see Copes et al, 2022). Although this affected participants' sense of agency and autonomy, they did not passively accept this stigma or the corresponding control over their lives.…”
Section: How Symbolic Boundaries Reduce Harmmentioning
confidence: 99%
“…The participants, however, found a way to turn dominant cultural stories of motherhood to their advantage. The women said that romantic partners, typically men, often tried to control how much, how, and when they used meth (see Copes et al, 2022). At times this meant men sought to encourage them to use more, but other times men tried to curtail their use.…”
Section: Emphasizing Motherhoodmentioning
confidence: 99%
“…A recent photo ethnographic study on cisgender men and women who used meth in rural Alabama, showed how gendered narratives of meth use can shape sexual interactions (Copes et al, 2021). Men in their study described meth as a "sex drug" which influenced how they approached women and also used it as justification of violence against women.…”
Section: Women's Sexualized Roles In Illegal Drug Marketsmentioning
confidence: 99%
“…Descriptions of how men utilized the market to control and manipulate women into having sex with them was highly common (cf. Copes et al, 2021). For example, Ally witnessed her male roommates' revolving door of women coming over for meth: Evident in Ally's statement, men used meth to incentivize and coerce women into having transactional sex.…”
Section: Gendered Expectations and Sex-for-meth Interactionsmentioning
confidence: 99%
See 1 more Smart Citation